Handball Sport Development System In Indonesia - Mohammad Anjas Julio; Yunyun Yudiana; Boyke Mulyana (UNIVERSITAS NEGERI MAKASSAR, 2022)
Sports coaching and development programs require policies so that competitions are held to grow sports and ultimately become winners. Sports coaching and development must be managed using good management, in the parent sports organization and associations involved in developing professional sports. The purpose of this research is to examine the system of coaching and development of the sport of handball achievement in Indonesia, and to examine the relationship between the coaching and development system and the achievement of handball in Indonesia. This research method is descriptive with a correlational research design. The population of this study was coaches and BINPRES who took part in the XX PON in Papua in 2021 in the handball sport as many as 14 participants. The sampling technique in this study uses total sampling. The conclusion of this study is that the system of coaching and developing handball in Indonesia is very good, and this research shows that the system of coaching and development has a significant relationship with the achievement of handball in Indonesia. This is indicated by the results of a significance of 0.001 and an R of 0.962 or based on the degree of relationship as a perfect correlation.